EXTERNAL BREATH FUNCTION AND HEART RATE VARIABILITY PARAMETERS DEPENDING ON SEVERITY AND DURATION OF BRONCHIAL ASTMA - Pasko, O.M.; Yabluchansky, M.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Aim of the study was to establish connection of heart rate variability (HRV) and external breath function (EBF) in  patients with bronchial asthma (BA) with different severity and duration of BA. 61 patients with BA I-IV of the average age 53+18 years were surveyed in out-patient conditions. The EBF was estimated with the help of respiratory movements frequency per one minute (RMF), forced lung vital capacity (FLVC) and forced exhalation volume per 1 second (FEV1). For the HRV analysis heart beat frequency per one minute (HBF); spectrum total power (TP); spectrum power of very low, low, high frequencies (VLF, LF, HF) and low-frequency/high-frequency spectrum power ratio (LF/HF) were used. The increase of severity and duration BA is characterized by the coordinated changes of parameters EBF and HRV with authentic reduction of  FEV1 and TP HRV basically by means of HF, that is shown by LF/HF growth, and activation of sympathetic part of nervous system.